Arqueología con pertenencia social: la experiencia de la Sección de Arqueología con la comunidad de Golfito - Arias Quirós, Ana Cecilia (Universidad de Costa Rica, 2013)
The Department of Archaeology at the University of Costa Rica inicipó in 1996 a research project in the Golfo Dulce, south of the country, called "Research proposal for understanding the archaeological potential of the Osa Peninsula." At first, the article the Programme who directs the Center for Research in Marine Biology and Limnology, CIMAR, which is, "Integrated Research for Sustainable Development and Environmental Management of Coastal Systems of the Golfo Dulce, Costa Rica" , by its multidisciplinary nature, thus favoring, work with professionals from disciplines such as biology, geography and geology, as well as interagency and international opportunities that the program would provide, for example, the alpha network system and bilateral agreements with the University of Bremen (Germany), the University of Bergen (Norway), La Rochelle University (France) and the University of Toledo, Ohio (USA). Then for reasons of logistics and budgetary began an independent path.